The Lost Soul of Bandung in Indonesia’s Foreign Policy - Mulia, Aldi Haydar; Prastita, Rama Ardhia; Arnanda, Muhammad Daffa (Global South Review, 2025)
This article explores Indonesia's evolving role in global diplomacy, focusing on its historical leadership in the Bandung Conference and the subsequent challenges it has faced in maintaining that influence. The study examines two central questions: why the appeal of the Bandung Conference had not elevated Indonesia into prominence, and what challenges and opportunities ahead that should be considered to resolve the issue. Through a qualitative approach, the research analyzes the transformation of Indonesian foreign policy, examining the shift from Sukarno’s commitment to Bandung’s principles to the pragmatic diplomacy of Suharto and beyond. The study draws on the concept of normative power to explain how Indonesia's diplomatic aspirations have often lacked clarity and coherence. The findings highlight the continued relevance of Bandung’s vision in challenging neo-colonial structures, but also underscore the obstacles Indonesia faces, including domestic political instability and inconsistent foreign policy. While cautiously optimistic about Indonesia’s potential to revitalize Bandung’s legacy, the article concludes that achieving this requires clear leadership and alignment with contemporary global issues. Ultimately, this paper contributes to understanding the complexities of postcolonial diplomacy and the future of middle power states, with practical implications for Indonesia's role in a multipolar world.